Origin discrimination of protected geographical indication (PGI) Sunite lamb using fingerprinting technology coupled with machine learning - Ruting Zhao; Jishi Wang; Xiaoxia Liu; Yanyun Wang; Yan Zhao; Zeying He; Shuming Yang (Food Chemistry, 2026)

Making waves: Impaired osmotic reserve by chemical exposure amplifies vulnerability of estuarine organisms to climate-driven salinity shifts - Ruting Yang; Dali Wang; Yao-Ping Wang; Muting Yan; Huizhen Li; Jing You (Water Research, 2026)

Spatiotemporal Changes and Climate Driving Factors of Compound Precipitation‐Temperature Extreme Events Across Global Land Areas - Ruting Yang; Silong Zhang; Xiongpeng Tang; Chao Gao; Haibin Zhang; Xin Yin; Yanli Liu (International Journal of Climatology, 2026)
Compound climate extremes, such as concurrent precipitation and temperature extremes, cause significant impacts on socioeconomics and ecosystems. Recent studies have made substantial progress in the specific type of compound extremes; however, characteristics of different types of compound precipitation and temperature extremes across the globe and their driving mechanisms remain limited understood. This study investigated characteristics of compound extremes including dry‐warm (DW), wet‐warm (WW), dry‐cold (DC), and wet‐cold (WC) combinations in annual, JJA (June, July, and August), and DJF (December, January, and February) occurrences during 1901–2024 across global land areas and their relationships with climate variability modes. Results indicated that the spatial distribution of the frequency of DW (WW) showed a similar pattern to that of WC (DC). The overall frequency of compound warm‐related (cold‐related) extremes successively increased (increased and then decreased) from the period 1901–1941 to the period 1983–2024. The spatial extent of compound warm‐related (cold‐related) extremes presented an increasing (decreasing) trend in all the continents over the past 124 years. The areas with positive (negative) precipitation‐temperature correlation showed high frequency of WW and DC (DW and WC). The areas with positive (negative) dependence between precipitation and temperature extremes of DW and WC showed negative (positive) dependence between the two extremes of WW and DC, except for central Asia where the two extremes showed positive dependence in the four compound extremes. During 1901–2024, El Niño (La Niña) tended to induce annual high (low) DW and low (high) WC occurrences in northern South America, southern and central Africa, southern Asia, eastern Australia, and northwestern North America and high (low) WW and low (high) DC occurrences in South America, Africa, western and southern Asia, southern Europe, western North America, and western Australia. The positive (negative) Dipole Mode Index tended to induce high occurrences of compound warm‐related (cold‐related) extremes in most global land areas. The positive North Atlantic Oscillation (NAO) tended to induce high WW occurrences and low DC occurrences in central and northern Europe, northern and central‐eastern Asia, and eastern North America, especially during DJF. This study provides scientific insights into the spatiotemporal characteristics and driving mechanisms of different compound extremes across the globe under a changing climate.

A Global Assessment of Climate Change and Anthropogenic Effects on Changes in Streamflow - Ruting Yang; Xiongpeng Tang; Silong Zhang; Chao Gao; Yanli Liu; Shuaifeng Lu; Fubo Zhao; Bikui Zhao (Water Resources Management, 2026)

Class-Specific Antihypertensives and Alzheimer’s Disease: Genotype- and Hypertension-Stratified Analysis - Dehao Yang; Ruting Wei; Jinrong Zhu; Jiaxuan Chen; Shiyue Wang; Hejia Cai; Bo Zhang; Bingxin Teng; Bohao Li; Xiaoya Xie; Suwen Huang; Yiyun Weng; et al. (Molecular Neurobiology, 2026)

A bibliometric assessment of the science and practice of blue–green space (BGS): hot spots, lacunae, and opportunities - Bo Mu; Ruting Zhao; Yang Liu; Enkai Xu; Yali Zhang; Hong Wei; Guohang Tian (Socio-Ecological Practice Research, 2024)

Cell-nanocarrier drug delivery system: a promising strategy for cancer therapy - Jiefen Yang; Xiongxi Shi; Yanting Kuang; Ruting Wei; Lanni Feng; Jianming Chen; Xin Wu (Drug Delivery and Translational Research, 2024)